2016
DOI: 10.1016/j.vetpar.2016.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Synergism between ivermectin and the tyrosine kinase/ P -glycoprotein inhibitor crizotinib against Haemonchus contortus larvae in vitro

Abstract: 2 Graphical abstract3 Highlights:-we examined interaction of P-gp inhibitor crizotinib with ivermectin in Haemonchus contortus larvae in vitro -crizotinib increased the toxicity of ivermectin towards a resistant isolate in migration assays -less synergism observed in larval development assays -assay differences suggest life-stage specific patterns of ivermectin / P-gp interaction.-study highlights potential of P-gp inhibitors to reverse ivermectin resistance AbstractAnthelmintic resistance is a major problem i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Crizotinib inhibits the P-gp, OCT1/2, OATPB1/3, OATP2B1, OATP4C1, multidrug and toxin extrusion protein (MATE1), and MATE2-K, but not OAT1/3, or bile salt export pump transporter (BSEP). 11,12,49,50 Razaet al 51 reported that crizotinib significantly increased the sensitivity of P-gp over-expressing cells in response to doxorubicin and paclitaxel. Therefore, crizotinib may have the potential to increase the plasma concentrations of co-administered P-gp substrates, and close clinical surveillance is recommended when crizotinib is administered with these agents.…”
Section: Crizotinibmentioning
confidence: 99%
“…Crizotinib inhibits the P-gp, OCT1/2, OATPB1/3, OATP2B1, OATP4C1, multidrug and toxin extrusion protein (MATE1), and MATE2-K, but not OAT1/3, or bile salt export pump transporter (BSEP). 11,12,49,50 Razaet al 51 reported that crizotinib significantly increased the sensitivity of P-gp over-expressing cells in response to doxorubicin and paclitaxel. Therefore, crizotinib may have the potential to increase the plasma concentrations of co-administered P-gp substrates, and close clinical surveillance is recommended when crizotinib is administered with these agents.…”
Section: Crizotinibmentioning
confidence: 99%
“…The induction of changes in the functions of metabolic enzymes (or in pumps involved in the removal and inactivation of a drug) may trigger a mechanism of drug resistance. For example, nematodes from the Trichostrongylidae family are resistant to macrocyclic lactones in which the overexpression of genes encoding ABC transporters responsible for removing the pharmaceutical from the parasite has been observed (Raza et al, 2016a(Raza et al, , 2016b(Raza et al, , 2016c.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ABC transporters might be involved in the active efflux of anthelmintic drugs away from their target sites, resulting in decreased drug concentration and increased parasite survival ( Figure 1 ). This has been shown by the increased efficacy of anthelmintic drugs in nematodes using multidrug resistance inhibitors (MDRIs), which inhibit the activity of ABC transporters [ 14 , 15 ]. In addition, it has been suggested that anthelmintics such as ivermectin (IVM), levamisole (LEV) and thiabendazole (TBZ) are substrates of ABC transporters [ 12 , 16 ], and there is considerable evidence that exposure to anthelmintics also modulates the expression patterns of different ABC transporters in nematodes [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%